ASSISTANCE IN PREPARING A SOCIAL BUSINESS MODEL CANVAS IN ENCOURAGING WASTE MANAGEMENT PRODUCTIVITY - Asiyah, Binti Nur; Wahyudi, Amin; Launiya, Khiyaratul (International Journal of Engagement and Empowerment (IJE2), 2024)
Waste management could be more optimal. Waste is managed without planning and without seeing the social potential in the community. This paper analyzes the assistance in preparing Social Business Model Canvas to encourage the productivity of waste management teams. The method of writing this paper is carried out with Asset Based Community Development accompanying the compilation of Social Business Model Canvas. The results of this paper show that 7 Waste Management Teams have been arranged in a Social Business Model Canva. The productivity of the waste management team will be based on the Social Business Model Canvas, which will inspire people to care about waste management, personal waste, the environment, and the wider community. The practical implications of this paper encourage the government, through consultants, to maximize assistance in the implementation of waste management by paying attention to the Social Business Model Canvas